The Antioxidant Effect of Sidr (Zizyphusspina-Christi) Leaf Extract Helping to Improve the Scopolamine Induced Memory Impairment in Male Rats: Antioxidant Sidr (Zizyphusspina-christi) scopolamine induced memory impairment - Mustafa Noutarki; Mahbubeh Setorki; Zahra Hooshmandi (Iranian Journal of Pharmaceutical Sciences, 2017)
Medicinal plants have attracted global attention due to their high levels of antioxidant components for prohibiting or improving various diseases including brain and memory disorders. This study was designed to investigate if the antioxidant effect of Sidr (Zizyphusspina-christi) extract can help to improve the scopolamine induced impairment of memory in Wistar rats. Animals were randomly divided into 6 groups: Control, Scopolamine at 1 mg/kg, Scopolamine+50 mg/kg Sidr extract (Zsc50+sco), Scopolamine+100 mg/kg Sidr extract (Zsc100+sco), Scopolamine+200 mg/kg Sidr extract (Zsc200+sco) and Scopolamine+diazepam at 1 mg/kgbw (D+sco). Antioxidant activity and total phenolic content of Z. spina-christi as well as the Passive avoidance test, antioxidant capacity and MDA level of plasma and brain were evaluated.Scopolamine increased the recorded initial latencies but decrease the step-through latency in comparison with those of control group. The use of Sidr at 50, 100 and 200 mg/kg attenuate these abnormalities and the impaired passive avoidance memory was improved. Although scopolamine didn’t cause any change in the antioxidant capacity plasma and brain, it increased the MDA level of plasma and brain tissues. Also use of Sidr increased the antioxidant capacity and decreased the MDA level of plasma and brain tissues.The results suggest that Z. SC might act to attenuate scopolamine induced brain and memory impairments due to its high antioxidant contents. The separation of the specific compound responsible for observed antioxidant activity with protective effect against brain and memory disorders still need further researches.